Integrating STEM into Middle School Science through Smart Agriculture Projects - Wulanningtyas, Melania Eva; Hutabarat, Christina Ester Manthalina; Arfin, Arfin; Fauzi, Rizky Reza; Situmorang, Risya Pramana (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
The STEM Center for Teaching and Learning at Parahyangan Catholic University, in collaboration with Ruang Bergerak, organized a community outreach program as part of its Tridharma commitment. The program included seminars and hands-on training for science teachers from the MGMP (Subject Teachers Forum) in Salatiga. The goal was to introduce project-based learning (PBL) methods using a STEM (Science, Technology, Engineering, and Mathematics) approach within the context of smart agriculture. This initiative aimed to help teachers foster essential 21st-century skills—such as problem-solving, critical thinking, and collaboration—that had noticeably declined during the pandemic. This program was designed to support teachers in implementing integrated, project-based learning that not only crosses disciplinary boundaries but also ties directly to measurable learning outcomes. Teachers were encouraged to connect the projects to real-world contexts, making assessments more meaningful and relevant to each subject area. Additionally, the smart agriculture project served as a practical application of P5 (Proyek Penguatan Profil Pelajar Pancasila) under Indonesia’s Merdeka Curriculum. Teachers were given the flexibility to adapt the prototype projects for further development in their own schools, aligning with each school’s unique goals and agreements. Over the course of two days, participating teachers learned how to design and execute contextual, problem-based STEM projects. They gained hands-on experience with technologies like Arduino and agricultural sensors. The program consisted of two main phases, the first involved expert-led workshops, and the second focused on collaborative project design based on local agricultural challenges. Despite the limited time, the program successfully fostered collaboration among teachers and expanded their understanding of how integrated, STEM-based learning can support both academic goals and character development through P5.